Advances in raw material industries for sustainable development goals PROCEEDINGS OF THE XII RUSSIAN-GERMAN RAW MATERIALS CONFERENCE (SAINT-PETERSBURG, RUSSIA, 27-29 NOVEMBER 2019) - Litvinenko, Vladimir (Taylor & Francis, 2021)
"""Advances in Raw Material Industries for Sustainable Development Goals"" presents the results of joint scientific research conducted in the context of the Russian-German Raw Materials Forum. Today Russia and Germany are exploring various forms of cooperation in the field of mining, geology, mineralogy, mechanical engineering and energy. Russia and Germany are equally interested in expanding cooperation and modernizing the economy in terms of sustainable development. The main theme of this article collection is connected with existing business ventures and ideas from both Russia and Germany. In this book the authors regard complex processes in mining industry from various points of view, including: - modern technologies in prospecting, exploration and development of mineral resources - progressive methods of natural and industrial mineral raw materials processing - energy technologies and digital technologies for sustainable development - cutting-edge technologies and innovations in the oil and gas industry. Working with young researchers, supporting their individual professional development and creating conditions for their mobility and scientific cooperation are essential parts of Russian-German Raw Materials Forum founded in Dresden 13 years ago. This collection represents both willingness of young researchers to be involved in large-scale international projects like Russian-German Raw Material Forum and the results of their long and thorough work in the promising areas of cooperation between Russia and Germany."